A45 A NOVEL PH-SENSITIVE OPIOID ANALGESIC THAT SELECTIVELY INHIBITS NOCICEPTION IN DSS-INDUCED COLITIS. (4th March 2021) - Yu, Y; Jiménez-Vargas, N N; Tsang, Q K; Lopez Lopez, C; Jaramillo Polanco, J; Stein, C; Lomax, A E; Reed, D E; Bunnett, N; Vanner, S
Abstract: Background: Opioid drugs are used to treat pain in inflammatory bowel disease (IBD) but their side effects can cause serious morbidity. Therefore, we tested a novel opioid analgesic, ±)-N-(3-fluoro-1-phenethylpiperidine-4-yl)-N-phenylpropionamide (NFEPP) which selectively activates peripheral µ-opioid receptors at acidic pH, as occurs in inflamed tissue. Aims: Evaluate whether NFEPP causes analgesia in the inflamed colon of DSS-colitis mice using both in vitro and in vivo techniques. Methods: To measure the visceral motor reflex (VMR) in response to colorectal distention, EMG electrodes connected to a telemetric transmitter were implanted in mice (c57BL/6), after 10 days recovery acute dextran sodium sulfate (DSS) colitis was induced (5 days 2.5% DSS, 2 days water). VMR was measured 30 min after s.c. injection of vehicle or 0.2 mg/kg of NFEPP or fentanyl. Motility was assessed by fecal pellet count 1 hour after NFEPP. Colonic tissue pH was evaluated using the SNARF-4F-5 carboxylic acid probe. Excitability of mouse dorsal root ganglia (DRG) neurons was measured by recording the rheobase (minimum input current to fire an action potential) after superfusion of NFEPP (300 nM, 10 min) or vehicle at pH 6.5 or 7.4. Colonic afferent nerve responses to probing with a von Frey filament (1 gm) were examined before and after exposure to NFEPP (300 nM, 5 min superfusion) at pH 6.5 and 7.4 respectively. The data was analyzed with Welch's t-test, 1- or 2-way ANOVA with post hoc Dunnett or Bonferroni or Tukey's test. Results: NFEPP significantly inhibited the VMR in response to distension in mice with colitis compared to vehicle (decreased response by 65%, P<0.001). NFEPP had no effect in control mice. Conversely, fentanyl caused a similar decreased response in both groups (DSS 79% and control 67%, P<0.001). Pelleting was not affected by NFEPP injection in either group compared to vehicle. The pH measurement revealed a more acidic environment in DSS colonic tissue (ΔpH0.37±0.14, P<0.05) compared to controls. In patch-clamp studies, NFEPP decreased DRG excitability at pH 6.5 compared to the baseline and vehicle (increased rheobase 53.84%, P<0.01 and 36.36%, P<0.05 respectively) but had no effect at pH 7.4. In colonic afferent nerve recordings, NFEPP significantly attenuated afferent responses (28.9% P<0.01) to probing at pH 6.5 but also had no effect at pH 7.4. Conclusions: This pH-selective opioid agonist significantly inhibits pain at the site of inflammation where the tissue pH is acidic but has no effect in tissues where the pH is in the physiological range. Thus, NFEPP could be an effective opioid analgesic in IBD while being devoid of any unwanted side effects. Funding Agencies: CCC